Dietary Antarctic Krill Oil Enhances the Oral Bioavailability of Nobiletin but Has No Ideal Synergistic Effect on Improving Memory and Cognition Ability in Aβ 1–42 Induced Rats - Kong, Jing‐Ya; Wang, Cheng‐Cheng; Duan, Xue‐Feng; Shi, Hao‐Hao; Xue, Chang‐Hu; Wei, Zi‐Hao; Huang, Qing‐Rong; Zhang, Tian‐Tian; Wang, Yu‐Ming (European Journal of Lipid Science and Technology, 2022)
Abstract Nobiletin (Nob) is reported to exhibit neuroprotective properties, which is limited by its low oral bioavailability. Antarctic krill oil (AKO) is abundant in n‐3 polyunsaturated fatty acids in the form of phospholipids, which exhibit an amphiphilic property. It is unclear whether AKO can enhance the bioavailability of nobiletin to facilitate the combined effect on neuroprotection. In the present study, the absorption of Nob carried by AKO is significantly enhanced in contrast to that suspended in corn oil. Moreover, Aβ 1–42 injected rats are utilized to clarify the effect of the combination of Nob and AKO on improving the memory and learning ability. Results present that the combination of AKO and Nob significantly reverses the cognitive and learning defects induced by Aβ 1–42 injection, but does not have ideal synergistic effect compared to AKO or Nob alone treated groups. Further molecular experiments imply that the neuroprotective effect may be attributed to the reduction of oxidative stress, the inhibition of apoptosis and tau phosphorylation, as well as the improvement of the neurotrophic activity. This study provides scientific insights and theoretical guidance for the nutritional interventions of the combined development of nobiletin and AKO to prevent neuropsychiatric disorders.